2004
DOI: 10.1242/jcs.01371
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent subcellular translocation of Gqα in Drosophila photoreceptors is facilitated by the photoreceptor-specific myosin III NINAC

Abstract: We examine the light-dependent subcellular translocation of the visual Gqα protein between the signaling compartment, the rhabdomere and the cell body in Drosophila photoreceptors. We characterize the translocation of Gqα and provide the first evidence implicating the involvement of the photoreceptor-specific myosin III NINAC in Gqα transport. Translocation of Gqα from the rhabdomere to the cell body is rapid, taking less than 5 minutes. Higher light intensities increased the quantity of Gqα translocated out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
71
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 63 publications
6
71
1
Order By: Relevance
“…As expected, the light-dependent shuttling of the Drosophila Gα q is dependent on rhodopsin; however, it does not require other known signaling proteins, such as NORPA [118,183], Arr2, PKC, TRP, and TRPL [183]. Thus, there may be other signaling proteins that remain to be identified, which interact with rhodopsin and promote the movement of the Gα q .…”
Section: Long-term Adaptation Through Light-dependent Translocation Osupporting
confidence: 62%
See 3 more Smart Citations
“…As expected, the light-dependent shuttling of the Drosophila Gα q is dependent on rhodopsin; however, it does not require other known signaling proteins, such as NORPA [118,183], Arr2, PKC, TRP, and TRPL [183]. Thus, there may be other signaling proteins that remain to be identified, which interact with rhodopsin and promote the movement of the Gα q .…”
Section: Long-term Adaptation Through Light-dependent Translocation Osupporting
confidence: 62%
“…Consistent with this proposal, NINAC is required for translocation of the Gα q and Arr2 from the cell bodies to the rhabdomeres, but not for the movement out of the rhabdomeres [183,189]. However, trafficking of TRPL-eGFP out of the rhabdomeres is reported to be disrupted in the ninaC null mutant [188].…”
Section: Long-term Adaptation Through Light-dependent Translocation Omentioning
confidence: 59%
See 2 more Smart Citations
“…G-proteins mediate phototransduction signaling. Recent studies have revealed that transducin and G q translocate between the signaling compartments, and this plays a role in an adaptation mechanism (12)(13)(14). The other is visual arrestin that is responsible for termination of the photoresponse.…”
mentioning
confidence: 99%